13th International Ceramics Congress : proceedings of the 13th International Ceramics Congress, part of CIMTEC 2014-13th International Ceramics Congress and 6th Forum on New Materials, June 8-13, Montecatini Terme, Italy. Part E - Vincenzini, P., 1939-; Mathur, Sanjay; Colombo, Paolo; Berndt, Christopher C. (Advances in science and technology (Faenza, Italy), 2014)
Collection of selected, peer reviewed papers from the 13th International Ceramics Congress, part of CIMTEC 2014-13th International Ceramics Congress and 6th Forum on New Materials, June 8-13, 2014, Montecatini Terme, Italy. The 21 papers are grouped as follows: Chapter 1: Nanomaterials for Energy and Sustainability; Chapter 2: Porous Ceramics; Chapter 3: Ceramic Thin Films and Coatings.